Enhancing English Communication Competence for Tourism Professionals and Students in Banyuwangi: A Phenomenological Study - Rusmawan, Putu Ngurah; Kanom, Kanom; Setianingsih, Tri; Kamarudin, Kamarudin (JOLLT Journal of Languages and Language Teaching, 2025)
The study aimed to explore the essential competencies of hospitality professional and the vocational students in communication skills needed to effectively interact with tourists from diverse cultural backgrounds and enhance their overall travel experience. This study used a qualitative phenomenological approach. The data was collected through in-depth interviews, with tourism student, professional industry worker, and practitioner tourism industry in Banyuwangi, participatory observations which conducted across tourist spots and documentation. A comprehensive analysis of relevant educational resources and industry-specific documents were employed in this study. Findings reveal a significant gap between theoretical instruction and practical application in English real tourism industry workforce setting, which affects confidence and communication skills among tourism workers. It emphasizes the necessity of collaborative frameworks between educational institutions and tourism enterprises to align training with dynamic industry demands. These findings provide valuable insights for curriculum improvement and training initiatives to enhance the global competitiveness of tourism professionals, especially in communication skills.